Dampak Pandemi Covid-19 terhadap Jenis dan Frekuensi Konsumsi Pangan Pokok oleh Rumah Tangga Tani di Kota Kendari - Hastati Hastati; Haji Saediman; Idrus Salam (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study aims to determine the type and frequency of staple food consumption before and during the Covid-19 pandemic and to analyze the impact of the Covid-19 pandemic on the type and frequency of staple food consumption in urban farming households. The research location was chosen because it is one of the areas exposed to the Covid-19 pandemic, consists of various ethnic groups, produces and consumes multiple types of staple food, and includes urban areas. The sample in the study amounted to 80 respondents who were selected by the Proportionate Stratified Random Sampling method. Data analysis used descriptive statistics, Wilcoxon Signed-Rank test, and McNemar test. The results showed that both before and during the pandemic, rice was the staple food that was very dominantly consumed by farmers' households, followed by sago and cassava with much less frequency. The existence of local food is only as a complementary staple food. The type of staple food and the frequency of consumption before and during the pandemic did not change significantly. Considering the availability of local food and the dominant consumption of rice, efforts to diversify staple food consumption need to be encouraged by considering accessibility and aspects of its use so that it can be more accepted by the community, including the millennial generation.